The coming culture. Visual communication: a clear tool for a free access to resources and knowledge - Parisio, Enrico (DISEGNARECON, 2011)
Nowadays the technologic/communicative systems are self-sufficiency: we, the users, are a sort of a spread net to release messages. We are used by systems, we don’t apply them. We have to set the planning function in a context, which is completely turned upside down, compared with the past: basically designers should facilitate a very straight flow of information. “Let it be”, this is the password. The authority is replaced by neutral, by the occurring impersonal events, by plurality, by the collective. Today the one who designs, is a “no-author”, a no-subject, a “it”. Today a visual communication design competes not only with the new technology languages, but most of all with the more elaborated ones, which are set by real subjects, who experience new forms of social relations, aggregation, conflicts.